2019
DOI: 10.1001/jamaoncol.2019.3338
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Progression-Free Survival as a Treatment End Point Among Patients With Advanced Cancer

Abstract: IMPORTANCEIt is unclear whether patients with advanced cancer value surrogate end points, particularly progression-free survival (PFS). Despite this uncertainty, surrogate end points form the basis of regulatory approval for the majority of new cancer treatments.OBJECTIVE To summarize and qualitatively assess studies evaluating whether patients with advanced cancer understand and value PFS.EVIDENCE REVIEW MEDLINE, Embase, the Cochrane Database of Systematic Reviews, the Cochrane Central Register of Controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Therefore, PFS, which is also often used as an endpoint in clinical trials, was chosen as a benefit attribute. How to best explain PFS to patients requires further exploration, 51 but in our survey development process, the definition of PFS was tested with lung cancer patients and was found to be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PFS, which is also often used as an endpoint in clinical trials, was chosen as a benefit attribute. How to best explain PFS to patients requires further exploration, 51 but in our survey development process, the definition of PFS was tested with lung cancer patients and was found to be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…However, OS as the primary endpoint requires a large sample size and long follow-up time to observe the survival benefit, leading to high clinical development costs and delays in introducing novel drugs. When used as the primary endpoints in clinical trials, early efficacy endpoints such as progression-free survival (PFS) and event-free survival (EFS) may require a smaller sample size and shorter evaluation time than OS, and have been established in some malignancies [ 6 8 ]. Trial- and individual-level studies have demonstrated that 24-month PFS and EFS may be considered the early efficacy endpoints for OS in DLBCL [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regulators point to patient demand as justification. However, a recent systematic review questions whether patients value this endpoint 13. Studies examining this question differed in how they defined progression-free survival to patients, reflecting the inherent complexity of this endpoint and the challenge in interpreting changes, even for clinicians and researchers.…”
Section: Patient Benefitmentioning
confidence: 99%